High efficiency blue and green light-emitting diodes using ruddlesden–popper inorganic mixed halide perovskites with butylammonium interlayers - Vashishtha, Parth (2020)
Ruddlesden–Popper phase inorganic metal halide perovskites are promising candidates for efficient light-emitting diodes (LEDs) with high brightness and color purity. Here, we demonstrate LEDs made from in situ grown CsPbX3 quasi 2D/3D thin films that are color tunable across the entire visible spectrum. CsPbX3 nanosheets are used to produce RP phase perovskites using butylammonium as a separating ligand to create BA2Csn–1Pbn(Br/Y)3n+1 2D/3D mixed halide thin films, where Y = Cl or I. The number of CsPbBr3 monolayers in these crystals was optimized by changing the butylammonium concentration. We demonstrate a stable perovskite phase with thin emission line widths providing points covering the edge of the CIE triangle and a maximum red/green/blue coverage of ∼130% of the National Television System Committee color standard. Additionally, we are able to report record efficiencies for blue emitting perovskite nanocrystal LEDs with a maximum external quantum efficiency (EQE) of 2.4% and 6.2% at 465 and 487 nm and a maximum luminance of 3340 cd/m2. We also demonstrate efficient green LEDs with a maximum efficiency of 10.1% EQE, 23.3 cd/A and 9.8 lm/W at 16.3 mA/cm2.